Influência da irrigação com água salina em sistema consorciado milho/feijão-de-corda - Araújo, Ana Paula Bezerra de (2015)
Changes in the microclimate in a intercropping can also change the responses of plants to some abiotic factors, including, salinity. The aim of this study was to evaluate the influence of salinity of irrigation water on gas exchange, ion levels, growth, productivity and efficiency of land use in single and intercropped systems, using plant corn and beans-in-corda. The experiment was conducted for two years following a design in randomized blocks in split plots, and the plots formed by the year of cultivation (2012 and 2013), the subplots by salinity of irrigation water (0.9, 2.5 and 5.0 dS m-1), and the split of crop systems (bean-to-rope, corn and more bean-to-string corn in consortium). The irrigated crops were conducted during the dry seasons of the years 2012 and 2013, and samples were taken soil samples before and after each crop, and after the passage of the rainy seasons of 2013/2014. To facilitate the description of the results, the thesis was divided into two chapters. The first is related to growth and productivity. The variables analyzed were: biomass production, productivity and efficiency of land use. The second is related to gas and mineral nutrition exchanges. The variables analyzed were: stomatal conductance, photosynthesis, transpiration, water use efficiency, levels of Na+, K+ and Cl+ in the leaves and stem. The accumulation of salts in the soil increased in proportion to the electrical conductivity values of irrigation water, with the highest observed in maize, a fact explained by the longer cycle and increased the employed irrigation depth in this culture. Rainfall totals recorded in the rainy seasons of 2013 and 2014 were sufficient to promote the leaching of excess salts below the root zone of crops. The accumulation of salts in the soil did not influence gas exchange and efficiency of water use, but caused an increase in the levels of Na+ in the leaves and stems. Despite the differences observed in the levels of Na, one can not relate them the variables of gas exchange, since they were not affected by the irrigation water salinity. The effects of salts on the production of total biomass and productivity of the plants were more expressive in plants under monoculture, especially in the bean-to-rope culture. The microclimate condition of intercropping system may have contributed to reduce the influence of salinity on productivity, mainly of bean-to-rope culture, resulting in higher values of efficient land use.